A test for community saturation along the Himalayan bird diversity gradient, based on within‐species geographical variation. (12th November 2013) - Ghosh‐Harihar, Mousumi; Price, Trevor D.; Both, Christiaan
Summary The idea that ecological communities are unsaturated is central to many explanations for regional gradients in species diversity. We describe a test for differing degrees of saturation across a regional diversity gradient, based on within‐species geographical variation in ecological attributes. If communities in species‐poor regions are less saturated than communities in species‐rich regions, species that straddle both regions should have broader niches in species‐poor regions, exploiting resources that are consumed by other species in species‐rich regions. We studied 10 species of Old World leaf warblers that range across the Himalayas. Elevational range and feeding method showed niche contractions in the species‐poor north‐west Himalayas with respect to the species‐rich south‐east Himalayas, whereas prey size did not vary geographically. Niche contractions are contrary to the expectation of character release in depauperate environments, as has been shown, for example in mainland‐island comparisons. We show that arthropod abundances are likely a limiting resource, and that niche contractions are consistent with measurements of a narrowing of resource availability. Results suggest that north‐western warbler communities are at least as saturated as the south‐east and that lower resource diversity drives reduced species numbers.